2022
DOI: 10.1007/s13304-022-01310-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gynecological surgery under minimally invasive anesthesia: a prospective cohort study

Abstract: The purpose of this study is to assess the feasibility and the perioperative outcomes of laparoscopic gynecological surgery in regional anesthesia (RA) from the point of view of the surgeon, anesthesiologist and patient. This is a prospective cohort study comprising sixty-six women planned to undergo gynecologic laparoscopy surgery for benign pathology at tertiary care gynecolgical center of the University Federico II of Naples. Women were assigned, according to their preference, to either RA (Group A) or gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This represents a convincing result, especially if it is considered that a recent review with meta-analysis has demonstrated no significant advantages to using SA over GA for laparoscopic treatment of benign gynecological diseases [ 32 ]. On the other hand, a prospective study published by the same Group has reported how RA could be a viable option for well-selected patients affected by benign gynecological diseases [ 33 ]. In addition, the use of regional anesthesia is gaining more and more importance also in the field of obstetrics [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This represents a convincing result, especially if it is considered that a recent review with meta-analysis has demonstrated no significant advantages to using SA over GA for laparoscopic treatment of benign gynecological diseases [ 32 ]. On the other hand, a prospective study published by the same Group has reported how RA could be a viable option for well-selected patients affected by benign gynecological diseases [ 33 ]. In addition, the use of regional anesthesia is gaining more and more importance also in the field of obstetrics [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vital signs were monitored: SpO 2 , heart rate, and blood pressure every 5 min. As already reported by Giampaolino et al [5], in the sitting position, in group A, RA was performed at the T9-T10 or T10-T11 level. In the subarachnoid space after the vision of clear cerebrospinal fluid in the spinal needle 27 gauge, without letting out the cerebrospinal fluid, ropivacaine 0.375% 18 mg, sufentanil 7 μg, and clonidine 20 μg were injected.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, a range of minimally invasive anesthesiological approaches are employed in obstetrics and gynecology: these include neuraxial analgesia, patient-controlled epidural analgesia for labor [2], transversus abdominis plane block, which is commonly applied during obstetrics surgery, such as cesarean section, or during hysterectomy and laparoscopic oncological surgery [3], as well as multimodal local anesthesia performed during the hysteroscopic procedures [4]. “Minimally invasive” procedures performed in laparoscopy can be combined with a “minimally invasive” technique to achieve anesthesia, such as in regional anesthesia (RA) [5]. This technique lowers the risk of adverse effects in the postoperative period including the need for rescue analgesics and antiemetics, the risk of nosocomial infections, late mobilization, and late bowel canalization [1, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and not to be underestimated, is the benefit of SLL in planning of future fertility treatment, for example favoring the referral for IVF/ICSI for women deemed unlikely to conceive based on post-surgical laparoscopic appearance of the pelvis. The advent of mini-laparoscopy and the use of regional anesthesia for laparoscopic surgery, with rapid recovery time following day surgery, can encourage (in selected cases) this procedure ( 63 ).…”
Section: Adhesion Preventionmentioning
confidence: 99%